Methods to standardize dietary intake before performance testing - Jeacocke, N. A.; Burke, L. M. (International Journal of Sport Nutrition and Exercise Metabolism, 2010)
When testing is undertaken to monitor an athlete`s progress toward competition goals or the effect of an intervention on athletic outcomes, sport scientists should aim to minimize extraneous variables that influence the reliability, sensitivity, or validity of performance measurement. Dietary preparation is known to influence metabolism and exercise performance. Few studies, however, systematically investigate the outcomes of protocols that acutely control or standardize dietary intake in the hours and days before a performance trial. This review discusses the nutrients and dietary components that should be standardized before performance testing and reviews current approaches to achieving this. The replication of habitual diet or dietary practices, using tools such as food diaries or dietary recalls to aid compliance and monitoring, is a common strategy, and the use of education aids to help athletes achieve dietary targets offers a similarly low burden on the researcher. However, examination of dietary intake from real-life examples of these protocols reveals large variability between and within participants. Providing participants with prepackaged diets reduces this variability but can increase the burden on participants, as well as the researcher. Until studies can better quantify the effect of different protocols of dietary standardization on performance testing, sport scientists can only use a crude cost-benefit analysis to choose the protocols they implement. At the least, study reports should provide a more comprehensive description of the dietary-standardization protocols used in the research and the effect of these on the dietary intake of participants during the period of interest.